2005
DOI: 10.1007/s00775-005-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial di-iron proteins: solution characterization of four helix bundles containing two distinct types of inter-helical loops

Abstract: Peptide-based models have an enormous impact for the development of metalloprotein models, as they seem appropriate candidates to mimic both the structural characteristics and reactivity of the natural systems. Through the de novo design of four-helix bundles, we developed the DF (Due Ferri) family of artificial proteins, as models of di-iron and di-manganese metalloproteins. The goal of our research is to elucidate how the electrostatic environment, polarity and solvent accessibility of the metal-binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…High-affinity metal binding sites in some proteins are located at sequence segments with specific amino acid composition[63], and specific sequence motifs have been used for predicting metal-binding proteins[64,65]. It was also found that polarity and solvent accessibility of the binding site influences the functional properties of metal-binding proteins[66]. Therefore, our prediction results are consistent with these experimental findings.…”
Section: Resultssupporting
confidence: 84%
“…High-affinity metal binding sites in some proteins are located at sequence segments with specific amino acid composition[63], and specific sequence motifs have been used for predicting metal-binding proteins[64,65]. It was also found that polarity and solvent accessibility of the binding site influences the functional properties of metal-binding proteins[66]. Therefore, our prediction results are consistent with these experimental findings.…”
Section: Resultssupporting
confidence: 84%
“…Some of these simple designs have been used to bind hemes (Gibney and Dutton 2001), bacteriochlorophylls (Noy et al 2006), flavins (Sharp et al 1998), iron-sulphur clusters , quinones (Li et al 2005;Mennenga et al 2006;Hay et al 2007), amino acid radicals , carboxy-bridged dimetal complexes (Laplaza and Holm 2001;Maglio et al 2005;Wade et al 2006) and very recently the di-iron Fe 2 S 2 (CO) 6 complex which is a model of a hydrogenase catalytic site (A. Jones, P. L. Dutton, personal communication). In an elegant study of the de novo 4-helix bundle, heme-binding proteins, the spectroscopic and electrochemical properties of the bound heme could be varied to match the corresponding properties of the different natural heme proteins by systematically modifying the electrostatic interactions and protonation states of the residues neighbouring the heme (Shifman et al 2000;Gibney et al 2001).…”
Section: Protein Engineeringmentioning
confidence: 97%
“…This hairpin is repeated with pseudo-C 2 symmetry to form the second half of the site. DeGrado and Lombardi used this information to guide the design of a family of minimal models of diiron proteins -the Due-Ferri (DF) series [125][126][127][128][129][130][131][132]. The DF family is characterized by a four-helix bundle, which can be formed by individual helices, or by the dimerization of a helical hairpin, or by a single chain of amino acids.…”
Section: Diiron Model Proteins: the Due-ferri Familymentioning
confidence: 99%